Tinjauan Yuridis Kewenangan OJK Sebagai Penyidik Tunggal pada Sektor Keuangan Berdasarkan UU P2SK - Fadila Nur Febriyandari; Nynda Fatmawati Octarina (Indo Publishing, 2026)
The appointment of the Financial Services Authority (OJK) as the sole investigator in the financial sector represents a strategic step in strengthening law enforcement and regulatory oversight of financial services in Indonesia. This authority is granted under Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU PPSK), which authorizes OJK to conduct criminal investigations related to financial sector offenses. This study aims to analyze the legal foundation, relevance, and juridical implications of such investigative powers in relation to the rule of law and the Indonesian criminal justice system. Using a normative legal research method and statutory approach, the study finds that granting OJK exclusive investigative powers is a form of institutional reform intended to address enforcement fragmentation. However, it also raises challenges in terms of accountability, procedural safeguards, and institutional coordination with other law enforcement bodies such as the police and the prosecutor’s office. Therefore, further regulation and robust external oversight are essential to ensure that this authority is exercised in accordance with the principles of a state governed by law.